Eksperimen Pembelajaran Matematika Dengan Strategi Problem Possing Dan Problem Based Learning Terhadap Hasil Belajar Siswa Ditinjau Dari Motivasi Belajar Kelas Vii Mts Negeri 1 Surakarta Tahun Pelajaran 2016/2017 - Warih Ramdhani, Muhammad, Drs, Slamet H.W, M.M, M.Pd (2017)
ABSTRACT Muhammad Warih Ramdhani/ A410130013. MATHEMATICS LEARNING EXPERIMENTS WITH STRATEGY PROBLEM POSSING AND PROBLEM BASED LEARNING ON THE RESULTS OF MATHEMATICS LEARNING MOTIVATION VIEWED FROM STATE CLASS VIII MTS NEGERI 1 SURAKARTA. Skripsi.Mathematics Education, the Faculty of Education, University of Muhammadiyah Surakarta. December, 2016 The purpose of the research are to analyze: (1) the effect of learning strategies Problem Possing and Problem Based Learning on learning outcome; (2) the effect of student's motivation to learning outcome;(3) the interaction between learning strategy and learning motivation on learning outcomes. Type of research quantitative with quasi-experimental design.Sample were taken by Cluster random sampling of the population of the research was all students of class VII MTs Negeri 1 Surakarta in academic year 2016/2017. Data collection technique byusing questionnaire, test and documentation. Before to the analysis, first tested the normality and homogeneity test. The hypothesis test use unbalance two way analysis of variance with α= 5%. The results of this study showsed: (1) there was the effect of learning strategies Problem possing and Problem Based Learning on learning outcome; (2) there was effect of student's motivation to learning outcome; (3) there was not interaction between learning strategy and learning motivation on learning outcomes. Keyword: Problem Possing , learning outcome, Problem Based Learning, learning motivation